2021
DOI: 10.1002/lary.29661
|View full text |Cite
|
Sign up to set email alerts
|

Thyroarytenoid Muscle Gene Expression in a Rat Model of Early‐Onset Parkinson's Disease

Abstract: Objectives/Hypothesis: Voice disorders in Parkinson's disease (PD) are early-onset, manifest in the preclinical stages of the disease, and negatively impact quality of life. The complete loss of function in the PTEN-induced kinase 1 gene (Pink1) causes a genetic form of early-onset, autosomal recessive PD. Modeled after the human inherited mutation, the Pink1À/À rat demonstrates significant cranial sensorimotor dysfunction including declines in ultrasonic vocalizations. However, the underlying genetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…Bcl7a has been described as B-cell CLL/lymphoma7 protein family member A, and it is involved in PD through the TNF-α and NF-κB signaling axis ( Wischhof et al, 2017 ). The genetic deletion of Bcl7a in postmitotic neurons elicits motor abnormalities ( Lechner et al, 2021 ). These findings provide novel proof for neuroinflammation and neuroimmune as the crucial modulators for PD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl7a has been described as B-cell CLL/lymphoma7 protein family member A, and it is involved in PD through the TNF-α and NF-κB signaling axis ( Wischhof et al, 2017 ). The genetic deletion of Bcl7a in postmitotic neurons elicits motor abnormalities ( Lechner et al, 2021 ). These findings provide novel proof for neuroinflammation and neuroimmune as the crucial modulators for PD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…A limiting factor of the preferred kit was its inability to consistently provide sufficient total RNA without pooling muscle fibers ( pt = 3). Compelling evidence in other rat model studies has demonstrated the feasibility of successful RNA-Seq analysis using the Aurum Total RNA Fatty and Fibrous Tissue Kit 25, 34 . Due to the greater column capacity (100 mg) of the aforementioned kit, its application can be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than isolated ILM alone, they studied all the soft tissue associated with the VFs, including VF mucosa and respiratory epithelium. A recent Parkinson's study demonstrated RNA-Seq expression analysis from the rat TA; however, their sequencing strategy enabled the input of low-throughput RNA extracts 25 . This method, commonly known as TruSeq, requires a small sample size and has unique RNA specifications unamenable to other bulk RNA-Seq technologies 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A limiting factor of the preferred kit was its inability to consistently provide su cient total RNA without pooling muscle bers (pt = 3). Compelling evidence in other rat model studies has demonstrated the feasibility of successful RNA-Seq analysis using the Aurum Total RNA Fatty and Fibrous Tissue Kit 25,34 . Due to the greater column capacity (100 mg) of the aforementioned kit, its application can be assessed in future studies.…”
Section: Tablementioning
confidence: 99%
“…Rather than isolated ILM alone, they studied all the soft tissue associated with the VFs, including VF mucosa and respiratory epithelium. A recent Parkinson's study demonstrated RNA-Seq expression analysis from the rat TA; however, their sequencing strategy enabled the input of low-throughput RNA extracts 25 . This method, commonly known as TruSeq, requires a small sample size and has unique RNA speci cations unamenable to other bulk RNA-Seq technologies 26 .…”
Section: Introductionmentioning
confidence: 99%